ANALYSIS OF JOINT VILLAGE OWNED BUSINESS ENTITIES IN GOOD GOVERNANCE PERSPECTIVE (Case Study of BUMDesma Mandiri Sejahtera Pati) - Nabilla Apriliany Cantik Prameswari; Kushandajani - - (Journal of Politic and Government Studies, 2022)
This study discusses the analysis of the Village-Owned Enterprises Together with Mandiri Sejahtera Pati in the perspective of good governance. This is because in Pati Regency, in fact, each village already has its own BUMDes, but in practice the majority are still constrained by bad loans. A new breakthrough emerged by uniting several villages into a BUMDesma. BUMDesma Mandiri Sejahtera Pati is predicted to be the latest breakthrough for village business entities operating in the health sector. The problems studied arise to see how this BUMDesma manages its organization.The purpose of this study was to analyze the governance of BUMDesma Mandiri Sejahtera Pati in the perspective of good governance. The process of analyzing it, this study uses the theory of Good Governance from Dr. Sedarmayanti with the variables of Accountability, Transparency, and Participation. This study uses a qualitative descriptive method using data collection techniques carried out through the process of interviews, observation, and documentation.The results of the study indicate that the management of BUMDesma is still not running well. However, it is undeniable that there are several problems and obstacles faced, especially in terms of accountability, namely accountability and financial reporting, which so far are still being criticized by the management. In addition, there is still a lack of coordination between stakeholders which causes miscommunication between each other.Based on the results of the study, there is a conclusion that BUMDesma Mandiri Sejahtera Pati based on the Good Governance theory that the author uses, namely Accountability, Transparency, and Participation, overall BUMDesma is still lacking. The disadvantages of BUMDesma are the lack of coordination between members, unclear financial reports, GMS, and profit sharing problems. Suggestions for BUMDesma are to focus more on evaluating financial reporting and improving coordination between members to minimize information misunderstandings. Recommendations for further research so that they can see from other perspectives and for other areas that this research can be a reference in the formation of BUMDesma.